2020
DOI: 10.1186/s12986-020-00495-3
|View full text |Cite
|
Sign up to set email alerts
|

Remote ischaemic preconditioning influences the levels of acylcarnitines in vascular surgery: a randomised clinical trial

Abstract: Background Vascular surgery patients have reduced tissues` blood supply, which may lead to mitochondrial dysfunction and accumulation of acylcarnitines (ACs). It has been suggested that remote ischaemic preconditioning (RIPC) has its organ protective effect via promoting mitochondrial function. The aim of this study was to evaluate the effect of RIPC on the profile of ACs in the vascular surgery patients. Methods This is a randomised, sham-controlled, double-blinded, single-centre study. Patients undergoing … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 31 publications
(43 reference statements)
0
5
0
Order By: Relevance
“…A complete list of the analyzed metabolites is provided in Table 2 . All (acyl-) carnitines were excluded as they had been discussed in a separate paper by the same authors [ 5 ]. Forty-five more metabolites were excluded, as >33% of their pre- or postoperative values were below the level of detection (<LOD).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A complete list of the analyzed metabolites is provided in Table 2 . All (acyl-) carnitines were excluded as they had been discussed in a separate paper by the same authors [ 5 ]. Forty-five more metabolites were excluded, as >33% of their pre- or postoperative values were below the level of detection (<LOD).…”
Section: Resultsmentioning
confidence: 99%
“…From 1 January 2016, to 8 February 2018, a randomized sham-controlled double-blind clinical trial was conducted at Tartu University Hospital’s Clinic of Surgery, Department of Vascular Surgery [ 3 , 4 , 5 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Research has suggested that RIPC may have the potential to significantly mitigate inflammation related risks associated with interventions, thereby potentially enhancing clinical outcomes for LEAD patients [ 11 ]. In our previous research, we demonstrated that patients receiving RIPC prior to vascular surgery exhibited altered acylcarnitine levels, suggesting potential protective effects on mitochondrial function in LEAD patients [ 12 ]. Considering that percutaneous transluminal angioplasty (PTA) and digital subtraction angiography (DSA) are likely to introduce fewer confounders than open surgery in similar settings, we hypothesized that the metabolic changes induced by RIPC might be more pronounced in this context.…”
Section: Introductionmentioning
confidence: 99%